Penyakit Ginjal Kronis dengan Anemia, Hiperkalemia, dan Hipoalbuminemia pada Pasien Wanita 41 Tahun: A Case Report - Abdillah A.F Hasanusi; Susan Timisela (Pusat Riset dan Inovasi Nasional, 2025)
Chronic Kidney Disease (CKD) is a global health issue with an increasing prevalence each year. One of the most significant complications of CKD is anemia, which occurs due to decreased erythropoietin production as a result of kidney damage. Erythropoietin plays a vital role in stimulating red blood cell production, and its deficiency leads to decreased hemoglobin and hematocrit, worsening quality of life, increasing cardiovascular risk, and accelerating kidney disease progression. This case report presents a 41-year-old female with complaints of bilateral lower leg edema for one week, accompanied by weakness and repeated vomiting. The patient has a history of poorly controlled kidney failure. Physical examination revealed pale conjunctiva and leg edema, while vital signs showed hypertension (BP 160/80 mmHg). Laboratory results revealed severe anemia (Hb 3.3 g/dL, HCT 9.2%, erythrocytes 1,007,000/mm³), severe renal dysfunction (urea 401 mg/dL, creatinine 18 mg/dL), hypoalbuminemia (2.7 g/dL), hyperkalemia (K 5.3 mmol/L), and a decreased glomerular filtration rate (6.29 mL/min/1.73m²), indicating CKD stage 5. This clinical manifestation emphasizes the strong relationship between CKD and anemia due to erythropoietin deficiency, exacerbated by metabolic disturbances and fluid retention. Management includes anemia correction through blood transfusion, erythropoietin supplementation, electrolyte disturbance management, and renal replacement therapy such as hemodialysis. Early detection and routine CKD management are critical to prevent severe anemia and life-threatening systemic complications. This case report aims to serve as a reference for clinical practice in managing CKD and its complications.